FORMULASI PASTA GIGI EKSTRAK ETANOL KULIT BUAH COKLAT (Theobroma cacao L.) dengan VARIASI BAHAN PENGIKAT - Faradiba Faradiba; Ermina Pakki; Nurlela Djalal (As-Syifaa Jurnal Farmasi, 2009)
A study has been done on the formulation of ekstract etanol pericarpium cacao as tooth paste with various binder agent.  the aim was to determined a stable tooth paste formulation of ekstract etanol pericarpium cacao (Theobroma cacao L.) physically satble. Two formula have been made use different binder agent, they were Natrium Carboxymetylcellulosa and Tragakan. Then the evalution of physics stability made before and after accelerated storing at 5oC – 35oC in which the parameters were organoleptic, pH, viskosity and flow type. The result of organoleptic and pH test from both formula showed no different before and after accelerated storing. The statistic analysis of viscosity’s result on formula I not shown a significant difference, but formula II shown a significant difference. Rheogram’s result of formula I and II shown dilatan flow type. So we concluded that the most stable formula was formula I used Natrium Carboxymetylcellulosa binder agent because had nothing changed before and after accelerated storing. Key words : pericarpium cacao,tooth paste